ANALISIS WHISTLEBLOWING SYSTEM DAN KOMPETENSI APARATUR TERHADAP PENCEGAHAN FRAUD (Studi Empiris Pada Satuan Organisasi Perangkat Daerah Kabupaten Bengkalis) - Endang Sri Wahyuni; Tiara Nova (Inovbiz: Jurnal Inovasi Bisnis, 2018)
The purpose of this study was to test the analysis whistleblowing system and the competence of apparatus to the fraud prevention. Object of this research is all SOPD of Bengkalis Regency. The data use in this research are primary data with analytical method is multiple regression analysis. The results of this research showed there is whistleblowing system and the competene of apparatus to the fraud prevention. Based on the research it was concluded that the determination coefficient is 70,6%. It means that 70,6% of the fraud prevention can be explained by the variable whistleblowing system and the competence of apparatus. While 29,4% is explained by other variables outside the model.